HUBUNGAN KEAKTIFAN DATANG KE POSYANDU DENGAN KUALITAS HIDUP LANJUT USIA WANITA DI DAERAH BINAAN PUSKESMAS PARIT H. HUSIN II PONTIANAK - Saleh, Ismael; Abrori, Abrori; Arbi’ah, Siti (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2016)
Menopause is a period that causes women experience both physical and psychological disorders. An optimal quality of like for the elderly could be interpreted as a functional condition at the maximum conditions so that they can enjoy their old age with a meaningful, happy, useful and quality of life.  If the quality of life of the elderly decreases, it will increase the morbidity and mortality of elderly. In July 2015, the morbidity of elderly who visited Puskesmas counted to 377 elderly consisted of 169 elderly men and 209 erlderly women. Additionally, in August 2015, the morbidity of elderly who visited Puskesmas were 474 elderly consisted of 223 elderly men and 251 elderly women. There was an increase number of elderly  visit in Augustby 6,25% from July  2015.The purpose of this study was to determine the relationship of theelderly activeness in visiting health center and the quality of life of elderly women in target areas at Puskesmas Parit H. Husin II Pontianak. This study was conducted by using analytical descriptive correlational design. The samples are 86 people taken from convenience sampling technique. The statistical test used is the Mann Whitney test with reliability rate of 95%.The results showed that there is no significant relationship between the elderly health visit(p value=0,449), social domain (p value=0,972),  environmental domain (p value=0,679), and the quality of life of physical health domain.Based on the findings, it is suggested to improve the education and socialization of the importance of Posyandu among elderly people to visit Posyandu maximally in order to improve the standard of life for the elderly in living their old age. Keywords       : elderly activeness, health center, Quality of Life